Grandparental genotyping enhances exome variant interpretation. Issue 4 (6th February 2020) - Daum, Hagit; Mor‐Shaked, Hagar; Ta‐Shma, Asaf; Shaag, Avraham; Silverstein, Shira; Shohat, Mordechai; Elpeleg, Orly; Meiner, Vardiella; Harel, Tamar
Abstract: Trio exome sequencing is a powerful tool in the molecular investigation of monogenic disorders and provides an incremental diagnostic yield over proband‐only sequencing, mainly due to the rapid identification of de novo disease‐causing variants. However, heterozygous variants inherited from unaffected parents may be inadvertently dismissed, although multiple explanations are available for such scenarios including mosaicism in the parent, incomplete penetrance, imprinting, or skewed X‐inactivation. We report three probands, in which a pathogenic or likely pathogenic variant was identified upon exome sequencing, yet was inherited from an unaffected parent. Segregation of the variants (in NOTCH1, PHF6, and SOX10 ) in the grandparent generation revealed that the variant was de novo in each case. Additionally, one proband had skewed X‐inactivation. We discuss the possible genetic mechanism in each case, and urge caution in data interpretation of exome sequencing data. We illustrate the utility of expanding segregation studies to the grandparent generation and demonstrate the impact on exome interpretation strategies, by showing that objective genotype data can overcome subjective parental report of lack of symptoms.